2015
DOI: 10.1001/jamapsychiatry.2014.2162
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lisdexamfetamine for Treatment of Adults With Moderate to Severe Binge-Eating Disorder

Abstract: IMPORTANCE Binge-eating disorder (BED), a public health problem associated with psychopathological symptoms and obesity and possibly with metabolic syndrome, lacks approved pharmacotherapies.OBJECTIVE To examine the efficacy and safety of lisdexamfetamine dimesylate, a dextroamphetamine prodrug, to treat moderate to severe BED. DESIGN, SETTING, AND PARTICIPANTSWe performed a randomized, double-blind, parallel-group, forced dose titration, placebo-controlled clinical trial at 30 sites from May 10, 2011, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
255
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(278 citation statements)
references
References 62 publications
19
255
4
Order By: Relevance
“…Lisdexamfetamine was already used for the treatment of attention deficit hyperactivity disorder. Weight loss in an 8-week study was 4.2 kg higher in subjects treated with lisdexamfetamine than in those treated with placebo [48]. Eleven-and twelve-week studies have recorded weight losses of between 5.2 and 6.25% [49].…”
Section: Eating Disordersmentioning
confidence: 95%
“…Lisdexamfetamine was already used for the treatment of attention deficit hyperactivity disorder. Weight loss in an 8-week study was 4.2 kg higher in subjects treated with lisdexamfetamine than in those treated with placebo [48]. Eleven-and twelve-week studies have recorded weight losses of between 5.2 and 6.25% [49].…”
Section: Eating Disordersmentioning
confidence: 95%
“…Stimulants were also used for BED. In a study conducted by McElroy et al, the use of lisamfetamine has been shown to reduce the frequency of exacerbations in adults with binge-eating disorders [8]. There are case reports about methylphenidate use for bulimia nervosa (but not for BED) in adults [9][10][11][12], but to our knowledge, to date, no case has been reported methylphenidate use for BED in children and adolescents in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Further analysis shows that the change in theta power is driven primarily by a decrease of power in the right inferior frontal gyrus after treatment (BA 47 or F8 electrode) as shown in with BED, also listed on the LDX prescription insert, include: dry mouth, headache, insomnia, decreased appetite, feeling jittery, anxiety, and increased heart rate and blood pressure [1] [7] [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was initially specified for the treatment of Attention Deficit Hyperactivity Disorder (ADHD), and later was proven to also have efficacy in limiting the occurrence of binge-eating behaviours [1] [4] [5] [6] [7].…”
mentioning
confidence: 99%